Acidic Oxygen Evolution Reaction Activity, Stability, and Durability of Copper and/or Manganese Cobalt Oxide Spinels - Liu, Christopher Pantayatiwong; Vang, Ethan Hwjchim; Priamushko, Tatiana; Roiron, Camille; Cherevko, Serhiy; Atanassov, Plamen (ACS Catalysis, 2025)
Cu and Mn was incorporated into Co spinels and the structural and electrochemical properties of the resulting materials were investigated. Cu and Mn were found to reside exclusively in the octahedral sites in the spinel lattice. The incorporation of Mn and especially Cu improved initial activity for the oxygen evolution reaction in an acidic environment. The Mn-containing catalysts demonstrated substantially improved potential cycling durability. This was explained through cyclic voltammetry and online inductively coupled plasma mass spectrometry (ICP-MS) by the role of Mn on limiting the oxidation of tetrahedrally coordinated Co2+. In potentiostatic conditions, however, pure Co spinel outperformed the multimetal oxides over time. In total, these findings stress the importance of stabilizing the tetrahedral Co2+ site through incorporation of other elements, and the improvements in electrochemical activity and stability that can thereby be realized.
CRIS-Team Scopus Importer:2025-05-09
Keywords: acidic oxygen evolution reaction; catalyst durability in acidic OER; cobalt spinels; in situ ICP-MS; metal oxide electrocatalysis; platinum-group-metal-free catalysis